1999
DOI: 10.1002/(sici)1098-2337(1999)25:2<113::aid-ab4>3.3.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone, aggressiveness, and antisocial personality

Abstract: Testosterone levels were examined in prisoners convicted of violent crimes (n = 13), in men previously convicted of violent crimes but currently not in prison (n = 15), in nonviolent alcoholics (n = 15), and in randomly selected control males (n = 16). Morning, afternoon, and evening testosterone levels were assessed after a minimum alcohol abstinence period of 24 hr. Violent and nonviolent men did not differ in plasma total testosterone level on any sampling occasion. In violent men, however, testosterone lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 27 publications
1
17
1
2
Order By: Relevance
“…In an item analysis to examine specific antisocial and aggressive behaviors, testosterone related most strongly to the tendency to protest or disobey commands (Olweus et al, 1988). These findings are consistent with other studies that found testosterone to be specifically related to externalizing symptoms involving aggression (Aromaki, Lindman, & Eriksson, 1999; Pajer et al, 2006). Although it may be particularly fruitful to examine testosterone in conjunction with aggressive responses to dominance challenges, the links of testosterone with symptoms such as alcohol abuse suggest the importance of an ongoing focus on a range of behaviors beyond aggression.…”
Section: Dominance Behavioral System: Links To Psychopathologysupporting
confidence: 92%
“…In an item analysis to examine specific antisocial and aggressive behaviors, testosterone related most strongly to the tendency to protest or disobey commands (Olweus et al, 1988). These findings are consistent with other studies that found testosterone to be specifically related to externalizing symptoms involving aggression (Aromaki, Lindman, & Eriksson, 1999; Pajer et al, 2006). Although it may be particularly fruitful to examine testosterone in conjunction with aggressive responses to dominance challenges, the links of testosterone with symptoms such as alcohol abuse suggest the importance of an ongoing focus on a range of behaviors beyond aggression.…”
Section: Dominance Behavioral System: Links To Psychopathologysupporting
confidence: 92%
“…It is assumed that androgens, in particular testosterone, may play a role in the aetiology of aggression (6)(7)(8), non-aggressive forms of adolescent risk-taking (9,10) and, at least in hypogonadal men, mood-related variables such as depression or self-esteem (11)(12)(13). However, results have been inconsistent, with most studies finding at best small or moderate associations with androgens, often in clinical or atypical populations, e.g.…”
Section: Introductioncontrasting
confidence: 64%
“…All together, these data do not seem to reveal cycle-related fluctuations of physiological aggressiveness, in accord with the report of Dougherthy et al (1998). This seems to contradict the data from the literature reporting relationships between sexual hormone concentrations, in particular FT and E, and aggressive behavior in women (Jnoff-Gormain et al, 1981;Simon and Whalen, 1986;Olweus et al, 1988;Gladue, 1991;Leibenluft et al, 1994;Gerra et al, 1996Gerra et al, , 1997Gerra et al, , 1998Finkelstein et al, 1997;Aromaki et al, 1999;Van Herringen et al, 2000;Grieng et al, 2001;Thiblin and Parlklo, 2002). However, these data refer to elevated or pathological or provoked aggressiveness related to hormonal secretions or administration, while we investigated the possible hormonal background of fluctuations of normal aggressiveness during the normal menstrual cycles in subjects in resting conditions.…”
Section: Discussionmentioning
confidence: 71%
“…Also, it is well known that peripherally secreted hormones, including androgens, glucocorticoids and growth hormone and centrally secreted opioids influence the development and the degree of physiological and pathological aggressiveness in experimental animals (Grieng et al, 2001) and in humans (Olweus et al, 1988;Coccaro et al, 1997;Gerra et al, 1996Gerra et al, , 1997Gerra et al, , 1998Finkelstein et al, 1997;Archer et al, 1998;Aromaki et al, 1999;Van Herringen et al, 2000;Pope et al, 2000;Grieng et al, 2001;Thiblin and Parlklo, 2002;O'Connor et al, 2002;Eriksson et al, 2003;Rowe et al, 2004). Little is known about the influence that female sexual hormones exert on this behavioral parameter, even though in experimental animals of both sexes, especially in major primates, aggressive behavior has been linked to variations of prenatal and postnatal estrogen secretions (Simon and Whalen, 1986;Finkelstein et al, 1997;Girolami et al, 1997;Palanza et al, 1999;Toda et al, 2001).…”
Section: Introductionmentioning
confidence: 99%